2016
DOI: 10.18632/oncotarget.7600
|View full text |Cite
|
Sign up to set email alerts
|

p73 promotes glioblastoma cell invasion by directly activating POSTN (periostin) expression

Abstract: Glioblastoma Multiforme is one of the most highly metastatic cancers and constitutes 70% of all gliomas. Despite aggressive treatments these tumours have an exceptionally bad prognosis, mainly due to therapy resistance and tumour recurrence. Here we show that the transcription factor p73 confers an invasive phenotype by directly activating expression of POSTN (periostin, HGNC:16953) in glioblastoma cells. Knock down of endogenous p73 reduces invasiveness and chemo-resistance, and promotes differentiation in vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 121 publications
4
27
0
Order By: Relevance
“…p53 family can be considered among the most powerful family of genes for the wide range of functions covering from tumour suppression, homeostasis and development [1][2][3][4][5][6][7][8][9][10][11]. In this context the p53 family member p73 plays critical roles such as tumour suppression [12][13][14][15][16][17], neuronal development and differentiation [18][19][20][21][22][23][24], metabolic control [25][26][27][28][29][30][31][32][33], and spermatogenesis and the maintenance of male and female fertility [34][35][36][37]. However, despite the important effort placed in investigating p73 functioning, a full dissections of its transcriptional programme and a clearly distinction of this from the transcriptome of its sibling p53 has not been completely elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…p53 family can be considered among the most powerful family of genes for the wide range of functions covering from tumour suppression, homeostasis and development [1][2][3][4][5][6][7][8][9][10][11]. In this context the p53 family member p73 plays critical roles such as tumour suppression [12][13][14][15][16][17], neuronal development and differentiation [18][19][20][21][22][23][24], metabolic control [25][26][27][28][29][30][31][32][33], and spermatogenesis and the maintenance of male and female fertility [34][35][36][37]. However, despite the important effort placed in investigating p73 functioning, a full dissections of its transcriptional programme and a clearly distinction of this from the transcriptome of its sibling p53 has not been completely elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…In order to validate these transcriptional observations, the expression pattern of several of the corresponding protein products was assessed by IF microscopy. The DEGs examined included (1) TNFRSF12A (Fn14), which encodes a cell surface protein that binds the ligand TWEAK and is over-expressed in many human solid tumor types including GBM 31 , 32 ; (2) BMP-7, which encodes a member of the TGF-β superfamily implicated in glioma cell growth control and stem-like glioma cell properties 33 35 ; and (3) POSTN, which encodes a secreted matricellular protein overexpressed in GBM that binds integrins and plays a role in macrophage recruitment and glioma cell invasion 36 38 . In agreement with the mRNA expression analysis data, TNFRSF12A expression was not detected in canine tumor tissue (Supplementary Figure 2C ), BMP-7 expression was not detected in rat tumor tissue (Supplementary Figure 2D ), and POSTN expression was not detected in mouse tumor tissue (Supplementary Figure 2E ).…”
Section: Resultsmentioning
confidence: 99%
“…In contrast to individual studies that identified and validated one or a few genes, high-throughput techniques such as microarray and Next-Generation Sequencing have also been used to identify TAp73 target genes across the entire genome, mostly focusing on coding genes. Based on our search term and analysis criteria, 12 articles published between 2008 and 2018 reported genome-wide studies aimed at identifying genes regulated by TAp73 in cancer cells [42,45,91,103,[112][113][114][115][116][117][118][119]. These studies utilized various techniques such as microarray (six studies), RNA-Seq (one study), ChIP-on-ChIP (three studies), and ChIP-Seq (three studies).…”
Section: Targets Identified From Genome-wide Studies-similar To and Dmentioning
confidence: 99%
“…CDKN1A is a major target of p53 that induces cell cycle arrest upon DNA damage [123]. On the other hand, POSTN that codes for Periostin, activates the Akt-and FAK-mediated signaling pathways to promote cancer cell motility and the epithelial-mesenchymal transition [103]. Table 4.…”
Section: Targets Identified From Genome-wide Studies-similar To and Dmentioning
confidence: 99%